1987
DOI: 10.1111/j.1651-2227.1987.tb10415.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Malabsorption and Giardiasis in Basotho School Children

Abstract: The prevalence of primary, adult-type, lactose malabsorption was assessed by means of the hydrogen breath test after intake of 360 ml of full cream milk (approximately 18 g lactose) in 96 randomly selected Basotho school children, aged 5-15 years. Of 86 children who did not have diarrhoea in the previous week 82 (85%) were lactose malabsorbers, while 4 (5%) could not be classified because of undetectable hydrogen excretion. Milk intolerance presenting as diarrhoea was significantly (p less than 0.01) more comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
1
8
1
2
Order By: Relevance
“…While other studies have reported significant association of lactose intolerance with giardiasis [18,19], only one child in the current study was found to have giardiasis and she had no evidence of lactose intolerance. Possibly, this was because of a less sensitive method used (wet stool preparation), as the 'string test' of duodenal contents would have been more preferable.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…While other studies have reported significant association of lactose intolerance with giardiasis [18,19], only one child in the current study was found to have giardiasis and she had no evidence of lactose intolerance. Possibly, this was because of a less sensitive method used (wet stool preparation), as the 'string test' of duodenal contents would have been more preferable.…”
Section: Discussioncontrasting
confidence: 78%
“…In one study, milk intolerance presenting as diarrhoea was significantly more common in children with giardiasis [18]. Similarly, Pettoello and colleagues in Italy concluded that the occurrence of lactose malabsorption of nutritional relevance was common in children suffering or having suffered from giardiasis (45%) [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been proposed that infection with G. intestinalis interferes between the intestinal brush border enzymes and the disaccharides present in the diet. Therefore, the findings by Tolboom and others, 27 together with the subtle defects in breath hydrogen test results we found in asymptomatic children, suggest that lactose malabsorption may be more likely associated with the lost of lactase caused by diarrhea than the direct effects of Giardia.…”
Section: Discussionmentioning
confidence: 79%
“…Similar results were found by Gendrel and others, who reported that asymptomatic giardiasis does not increase the frequency of lactose intolerance in well-nourished children. 4 Furthermore, Tolboom and others 27 found that lactose malabsorption does not correlate with the presence of giardiasis, but milk intolerance manifested as diarrhea is more common in children with giardiasis than in healthy subjects. Because of the location of the disaccharidases in the intestinal brush border, any condition that damages its morphology (such as severe diarrhea), will result in a detrimental effect on these enzymes, and thus disaccharides absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation